Carrying the Cross : the autobiography of Bishop Matthew Oluremi Owadayo. - Owadayo, Matthew Oluremi ([Place of publication not identified] : [publisher not identified], 2014)
Born in Ifira-Akoko, Nigeria in 1939 Bishop Matthew Oluremi Owadayo was appointed Menís warden of Archbishop Vining Training Centre, Akure; preferred Cathedral Provost, and later Dean, Immanuel College of Theology, Ibadan. In December 1994, he was elected Bishop of the Diocese of Egba.
Cover; Title page; Copyright page; Contents; Dedication; Acknowledgements; Foreword 1; Foreword 2; Preface; 1. Early Childhood; Akokoland; My Family; My Birth; Idogun: Place of Refuge; 2. Getting Started: My Primary Education; United School, Ifira-Ipesi; St. Paul''s School, Idogun; 3. My Secondary Education; Divinely guided to Victory College; Changes within the Family; Journey to Victory College; A Mentor Indeed!; The Great Relief; Experience as a Houseboy; As a Journey Walker; Managing Jeers and Sneers; My Second Year; Confirmation; 1958 -- A Year of Rewarded Risks; 1959 -- Year of Destiny.
Includes bibliographical references and index.
Print version record.
Keywords: Owadayo, Matthew Oluremi, -- Bishop; Theology -- Nigeria; Bishops -- Nigeria -- Biography; Archbishop; Owadayo, Oluremi -- Biography; Theology; RELIGION -- Christianity -- Orthodox; Electronic books